Legal Certainty in the Resolution of Disputes in the Sharia Capital Market in Indonesia - Novea elysa Wardhani (Faculty of Law, Universitas Pekalongan, 2025)
This article examines the concept and implementation of legal certainty in the resolution of disputes in Indonesia's Sharia capital market. As part of the national financial system, the Sharia capital market adheres not only to general capital market regulations but also to Islamic legal principles. The article identifies normative and practical challenges in ensuring dispute resolution mechanisms that are consistent with both positive law and Islamic values. Using a normative juridical approach supported by secondary legal materials, this study reveals that legal certainty in the Sharia capital market is still evolving, particularly in terms of institutional authority, procedural clarity, and the enforceability of Sharia-based decisions. The role of the Indonesian Ulema Council (MUI), the Financial Services Authority (OJK), and religious arbitration institutions such as Basyarnas is analyzed in depth. The findings highlight the need for an integrated regulatory and institutional framework that ensures both compliance with Sharia and the protection of investor rights. The article concludes that the future of dispute resolution in the Sharia capital market depends on harmonizing positive law with Islamic jurisprudence to foster a more just, transparent, and legally certain investment climate.